PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nur Aini Widyawati; Dyah Fitriani (Jurnal Fokus Manajemen Bisnis, 2014)
This study aimed to examine the effect of investment decisions, financing decisions and dividend policy on firm value in the LQ-45 firm listed on the Indonesia Stock Exchange. Population as well as the sample in this study is the LQ-45 firm listed on the Indonesia Stock Exchange 2007-2011 period which has complete financial statements are expressed in dollars and pay dividends continuously over the study period, which amountedÂ  to 9 companies. The dependent variable used is the value of the company (PBV) while the independent variable is investment (PER), funding (DER) and dividend policy (DPR). In this study using a multiple linier regression and classical assumption. Assessment of the effect of independent variables on the dependent variable was partially or simulataneously, and analysis tools in this study using eviews. Partial results of the study showed that investment decisions have a significant effect on firm value, funding decisions have no significant effect on firm value and dividend policy has no significant effect on firm value.